Rate dependence of ultra high toughness cementitious composite under direct tension - Li, He-dong; Xu, Shi-lang (Journal of Zhejiang University. A. Science, 2016)
Ultra high toughness cementitious composite (UHTCC) usually shows strain hardening and multiple cracking under static tension loads. In practice, structures could be exposed to high strain rates during an earthquake. Whether UHTCC can maintain its unique properties and provide high structural performance under seismic loading rates largely determines whether it can successfully fulfil its intended function. To determine the rate dependence of UHTCC, uniaxial tensile tests with strain rates ranging from 4×10 −6 s −1 to 1×10 −1 s −1 were conducted with thin plates. The experimental results showed that UHTCC had significant strain hardening and excellent multiple cracking properties under all the rates tested. The ultimate tensile strain lay in the range of 3.7% to 4.1% and was almost immune to the change in strain rates. The rate of 1×10 −3 s −1 seemed to be a threshold for dynamic increase effects of the first crack tensile strength, elastic modulus, ultimate tensile strength, and energy absorption capability. When the strain rate was higher than the threshold, the dynamic increase effects became more pronounced. The energy absorption capability was much higher than that of concrete, and the average ultimate crack widths were controlled below 0.1 mm under all rates. Several fitting formulas were obtained based on the experimental results.